William Szekspir w postpamięciowym dyskursie o zagładzie (Politeja, 2015)
William Shakespeare and the Post-memorial Holocaust DiscourseThe aim of the paper is to discuss the role of literary output of William Shakespeare in post‑memorial discourse about Holocaust. It analyzes various culture texts (film and theater adaptations, memoirs, essays and short stories) devoted to Holocaust, which refer to the dramatic heritage of English playwright. It discusses the phenomena of post‑Holocaust Shakespearean theatre treated as a medium for commemoration of the past. It focuses on Shakespeare’s motifs in post‑Holocaust literature and film.